The Impact of Entrepreneurship on Sustainable Development (Entrepreneurship Journal for Finance and Business, 2025)
Sustainable development refers to the rational use and efficient investment of resources to ensure biological and environmental balance while preserving the rights of future generations. Entrepreneurship is a powerful and effective tool for achieving this development. The Iraqi Ministry of Planning has approved the 2030 Sustainable Development Strategy in accordance with the agenda launched by the United Nations. Therefore, this research aims to shed light on the available capabilities, challenges facing sustainable development, and the levels of achievement of its goals.Iraq is still lagging behind in achieving the seventeen Sustainable Development Goals, and this requires attention. A national strategy should be adopted to revitalize all sectors and encourage innovation, while supporting and improving youth training opportunities and creating job opportunities commensurate with their academic and professional qualifications. Work should also be done to achieve social peace and reform budgeting systems for programs to achieve the Sustainable Development Goals.